Emotion Regulation and Parent Co-Regulation in Children with Autism Spectrum Disorder - Ting, Victoria (J Autism Dev Disord, 2017)
Children with autism spectrum disorder (ASD) often exhibit emotional problems, which can be associated with emotion regulation (ER) difficulties. Parent co-regulation is often associated with child ER and emotional problems, though little work has been done with reference to youth with ASD. This study investigated the association among parent co-regulation, child ER, and internalizing and externalizing problems in 51 parents and school-aged children with ASD. Parent co-regulation strategies and scaffolding were not associated with parent-reported levels of child internalizing problems. Parent scaffolding and child ER predicted externalizing problems, after controlling for child age and IQ. Suggestions for future research on parent involvement in the emotional development of children with ASD are discussed, as well as implications for ER-focused interventions.